From Reaction to Renewal: Civil Islam and the Moral Resilience of Moderate Muslims in Post-212 Indonesia - Harsono, Jusuf (The review of faith & international affairs, 2026)
This article explores the moral and civic resilience of moderate Muslim actors in Indonesia in the aftermath of the polarizing Aksi 212 (212 Movement), a pivotal episode of religious populism. While many accounts suggest that Civil Islam has been marginalized by the rise of religious conservatism, this study argues that Indonesia’s moderate Islamic networks, particularly Nahdlatul Ulama (NU) and Muhammadiyah, have responded through symbolic adaptation, ethical reframing, and institutional renewal. Using a qualitative approach that combines discourse analysis and interpretive textual reading, and drawing on the frameworks of contentious politics, covenantal pluralism, and symbolic politics, this article demonstrates how moderate Muslims have actively reaffirmed inclusive religious narratives, utilized digital platforms, and reasserted democratic pluralism. Rather than retreating, Civil Islam has been adapted to uphold moral commitments in an increasingly polarized landscape. This study contributes to global discussions on the role of religious civil society in resisting populist threats and sustaining pluralistic democracy, particularly in the Global South.